Investigation of effect gate size's scaling in NMOSFET on current-voltage (I-V) characteristic / Mazuin Ab Rahman - Ab Rahman, Mazuin (2010)
MOSFET is metal oxide semiconductor field effect transistor have been scale down in the critical device parameter to achieve highest integration density and performance. Smaller size of transistor give higher speed, it is consumes very low power and has a high yield of working devices. This report present an investigation of effect gate size's scaling in NMOSFET on current-voltage (I-V) characteristic. The parameters understudy to investigate the effect on (I-V) characteristic is threshold voltage and saturation current. An initial research found that, among the process parameter involved in the manufacture of devices, gate length has the most influential effect on those parameter. This study showed that it is capable to fabricated transistor in the normal environment laboratory but it is difficult to get ideal transistor because of some limitation and factor. The study also proved that, producing MOSFET with gate lengths much smaller than micrometer is a challenge, and the difficulties of semiconductor device fabrication are always a limiting factor in advancing integrated circuit technology.